Canarium Parvum Leaf Essential Oil Supplemented in the Diet of Japanese Quails: Effect on Growth Performance, Nutrient Digestibility, Immune and Haematological Parameters - Alagbe John Olujimi (International Journal of Global Sustainable Research, 2025)
A 30 days study was carried out to determine the effect of dietary supplementation of Canarium parvum essential oil on the growth performance, nutrient digestibility, haematological and immune parameters of Japanese quails. A total of 150 2 weeks old Japanese quails (mixed sex) were randomly divided into five groups each with 50 birds. Each treatment group was further sub-divided in to five groups each with 10 chicks of comparable group weight. . Standard diet (Corn-soya meal based diet) was formulated according to the nutritional requirement for quails recommended by Nutritional Research Council (1994).. Quails had unlimited access to fresh water and feed. Average daily weight gain and average daily feed intake were higher in birds fed Canarium parvum essential oil (B, C, D and E) compared to control (group A) (p˂0.05). Dry matter, crude protein, crude fibre, ether extract and nitrogen free extract digestibility were higher among birds in group B, C, D and E compared to A (p˂0.05). Immunoglobulin A, G and M, protein and energy utilization were influenced (p˂0.05) by the treatment. Lipase count ranged from 28.59 - 36.71 ng/mL, amylase (181.3 - 238.9 ng/mL), amylase (0.97 to 1.45 ng/mL), energy intake (2814.8 - 2937.37 ME/kcal/bird) and protein intake (222.34 - 232.12 g/bird) were affected. Hematocrit, red blood cell, hemoglobin and total leucocyte count were significantly different (p˂0.05) among the groups. However, their values were within the established range for quails. It was concluded that Canarium parvum essential oil is rich in multiple bioactive compounds and can be supplemented in the diet of quails without compromising their performance and health state